2014
DOI: 10.3766/jaaa.25.4.3
|View full text |Cite
|
Sign up to set email alerts
|

Aural Rehabilitation through Music Workshops for Cochlear Implant Users

Abstract: The workshops proved to be an effective means of simultaneously encouraging music exploration in a social and safe environment and obtaining feedback on prototype rehabilitation materials. Survey data suggested that through group listening and practical activities, certain aspects of music can be accessible and rewarding through a CI, leading to positive changes in attitude and behavior toward music.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 13 publications
1
12
1
Order By: Relevance
“…The general increase in listening habits for both groups from T1 to T3 could be due to participation in a study that drew the participants' attention to musical stimuli. The 5 point scale used for evaluating listening habits had previously been used successfully to evaluate longer term changes in listening habits following a series of music workshops (van Besouw et al, 2014). However, in the present study, the options "monthly"…”
Section: Music Listening Habitscontrasting
confidence: 46%
See 2 more Smart Citations
“…The general increase in listening habits for both groups from T1 to T3 could be due to participation in a study that drew the participants' attention to musical stimuli. The 5 point scale used for evaluating listening habits had previously been used successfully to evaluate longer term changes in listening habits following a series of music workshops (van Besouw et al, 2014). However, in the present study, the options "monthly"…”
Section: Music Listening Habitscontrasting
confidence: 46%
“…Program" (IMAP) with adult CI users (Oliver, van Besouw, & Nicholls, 2012;van Besouw, Nicholls, Oliver, Hodkinson, & Grasmeder, 2014). In a series of initial consultations, adult CI users indicated that they not only wanted to improve their music perception abilities, but also wanted tools to help them (re)engage with music.…”
Section: Evaluation Of a Music Program For CI Usersmentioning
confidence: 99%
See 1 more Smart Citation
“…The first three workshops also included group listening exercises using selected tracks from the HOPE Notes DVD. The therapeutic value of the workshops was concurrently investigated and is reported in van Besouw et al (2014) …”
Section: Phase 2: Use Of Mock-up Appsmentioning
confidence: 99%
“…The Rhythm Tapster was designed to help users replicate rhythms with the aid of visual feedback. Rhythm is one of the most accessible aspects of music through a CI and the rhythm activities included in the workshops proved to be particularly successful (van Besouw et al, 2014). It was therefore anticipated that CI users would find the Pulse Tapster and Rhythm Tapster activities motivating and rewarding.…”
Section: Prototype Imapmentioning
confidence: 99%